2014
DOI: 10.1111/ffe.12210
|View full text |Cite
|
Sign up to set email alerts
|

Influence of severe shot peening on wear behaviour of an aluminium alloy

Abstract: Recent developments in shot peening demonstrate that it can be applied using unconventional parameters in order to obtain nanocrystals on a thin surface layer of the treated material. These microstructural modifications have shown to be able to induce superior fatigue and corrosion properties, but still few data are available about their effect on wear behaviour of the materials.In this study, four series of Al 6063 alloy specimens, as‐received, conventionally shot peened, severely shot peened and severely sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 19 publications
(36 reference statements)
2
13
0
Order By: Relevance
“…As shot peening inevitably modifies surface and subsurface properties as a function of peening parameters, it is important to elucidate the tribological behavior of shot-peened materials, which have not yet been fully understood in the literature [ 19 , 26 ]. Differing conclusions have been presented in the existing literature as some studies highlighted that shot peening improves the tribological behavior of materials [ 35 , 72 , 73 ], whereas others reported that shot peening detrimentally affects wear resistance [ 71 ]. The effect of shot peening on the friction and wear behavior of materials is still largely unexplored [ 26 ], and there has been an increasing interest on revealing the tribological behavior of shot peened materials [ 7 , 34 , 71 , 72 , 74 , 75 , 76 ].…”
Section: Introductionmentioning
confidence: 99%
“…As shot peening inevitably modifies surface and subsurface properties as a function of peening parameters, it is important to elucidate the tribological behavior of shot-peened materials, which have not yet been fully understood in the literature [ 19 , 26 ]. Differing conclusions have been presented in the existing literature as some studies highlighted that shot peening improves the tribological behavior of materials [ 35 , 72 , 73 ], whereas others reported that shot peening detrimentally affects wear resistance [ 71 ]. The effect of shot peening on the friction and wear behavior of materials is still largely unexplored [ 26 ], and there has been an increasing interest on revealing the tribological behavior of shot peened materials [ 7 , 34 , 71 , 72 , 74 , 75 , 76 ].…”
Section: Introductionmentioning
confidence: 99%
“…In SSP, the process parameters are set in a way to considerably increase the kinetic energy that is transmitted to the treated material in order to induce grain refinement. SSP has been applied to a wide class of materials including low alloy steels, stainless steels, cast iron and Al alloys [42][43][44][45][46][47][48]. This choice was motivated by reports on the favorable effects of conventional shot peening in improving limited fatigue properties of Mg alloys typically used in the automotive and aerospace industries [16,29,49,50].…”
Section: Introductionmentioning
confidence: 99%
“…Among a great variety of surface treatments, shot peening is one of the most widely used techniques to increase the resistance of metal parts to fatigue in a large range of industries, such as automotive, aerospace and petrochemical [7,8,9]. It consists of blasting high velocity small beads on the metal component to generate surface hardening and compressive residual stresses which oppose to the nucleation of cracks and also exert a closure effect on those cracks already nucleated, avoiding their propagation [10,11].…”
Section: Introductionmentioning
confidence: 99%